Behavior of Lime-Stabilized Red Bed Soil after Cyclic Wetting-Drying in Triaxial Tests and SEM Analysis - Zhengmin Song; Dewen Zhang; Yuncheng Mao; Yanhu Mu; Kun Zhang; Qinglong Zhang (Advances in Materials Science and Engineering)
Most red beds demonstrate inferior geotechnical properties in natural conditions and need to be improved when used as construction material. In this study, a serious of triaxial tests, permeability tests, and scanning electron microscopy (SEM) analysis were carried out on lime-stabilized and untreated red bed soil after experiencing different wetting-drying (W-D) cycles. The test results showed that, with the increase in the added lime, the shear strength, strength parameters (including the cohesion and the internal friction angle), and the shear modulus of red bed soil increased gradually. For the untreated specimens, the four parameters decreased considerably after experiencing W-D cycles, while for the lime-stabilized specimens, they generally increased with an increase in the W-D cycles. Without experiencing the W-D cycles, the permeability coefficient increased by two times after it was stabilized with 10% lime. But with an increase in the W-D cycles, the permeability coefficient of the untreated and lime-stabilized specimens continuously increased and significantly decreased, respectively. Finally, variations in microstructure of the red bed soil under the effects of the lime stabilization and W-D cycles were discussed based on the SEM analysis. The results may contribute to improvement of red bed soil when used as roadbed and airfield fillings.